Gas-cooled reactors today. Volume 1, proceedings of the conference held in Bristol on 20-24 September 1982. (British Nuclear Energy Society, 1982)
Papers are organised by the following session titles: 'Operating Experience' and 'Engineering Experience and Developments' including 'Active Waste Management', 'Plant Experience and Evolution', 'Insulation, Boilers and Vibration', 'Concrete and Steel Pressure Circuits', 'Mechanisms' and 'Applications and Future Concepts'.